A PENGARUH KONSUMSI BERAS UNTUK KELUARGA MISKIN DI KELURAHAN TELUK BAYUR KECAMATAN TELUK BAYUR KABUPATEN BERAU - Indriani, Ira (PRODI EKONOMI PEMBANGUNAN, STIE MUHAMMADIYAH TANJUNG REDEB, 2017)
The purpose of this study is to determine the effect of rice consumption for poor families in Teluk Bayur,Berau. The analytical tool used in this research is statistical analysis, including: multiple linear regression equation, correlation coefficient, coefficient of determination and F-statistic test (simultaneous test). Based on the results of this study it can be seen that the multiple linear regression equation regarding the number of poor households and the volume of raskin purchase to the level of raskin consumption in Bayur Bay Village is Y = 38.24 + 19.5X1 + 2.6X2. So the value of Fh is greater than Ft (20.93> 9.55), the hypothesis proposed in this study is accepted or it is proven that the number of poor households and the volume of raskin purchase significantly influence the level of raskin consumption in Bayur Bay Village. The classification and criteria of poor households should be the same guidance between the Teluk Bayur Village and the Central Bureau of Statistics of Berau District, in order to collect the data into a single vision and accuracy guaranteed.